The Impact of Capital Structure on the Performance of Chinese E-Commerce Industry Companies (2013–2019 Panel Data). (14th July 2022) - Zhang, Meng-Yao; Lin, Li-Wei; Chen, Huei-Ping; Zhao, Xuan-Ze
Abstract : This research examined how to estimate performance in China's e-commerce industry, by taking 2013–2019 e-commerce listed companies as the research samples and using an empirical research method to study the relationship between capital structure and firm performance. The empirical results show that the debt-to-asset ratio and the long-term interest-bearing debt ratio have a negative impact on firm performance, but the impact of the long-term interest-bearing debt ratio is not significant. Moreover, the short-term interest-bearing debt ratio and the total asset turnover ratio have a positive impact on firm performance, while the impacts of the current assets ratio and intangible assets ratio on firm performance are not significant. The following suggestions are drawn from the results in order of importance. (1) Enterprises should maintain a reasonable debt-to-assets ratio and a stable capital structure and appropriately increase the proportion of short-term liabilities. (2) Firms should moderately invest to expand their scale and improve their profitability, so as to increase retained earnings and develop internal financing channels.